Sosialisasi Pajak Daerah Pajak Bumi dan Bangunan (PBB) serta Pajak Kendaraan Bermotor (PKB) - Amri Amrulloh; Lely Kumalawati; Halleina Rejeki Putri Hartono; Yopie Diondy Kurniawan; Khirana Kusumastutie (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Regional taxes, especially the Land and Building Tax (PBB) and Motor Vehicle Tax (PKB), have an important role in increasing Regional Original Revenue (PAD) and supporting infrastructure development and public services. Socialization activities carried out in RT. 42 RW. 13 Taman Village, Madiun City, aims to increase public awareness and compliance in paying taxes. Through seminars, direct counseling, as well as print and digital media, this socialization provides information on tax obligations and tax benefits for regional development. The results of the socialization show an increase in public understanding of the tax function, although there are still obstacles, such as a lack of in-depth understanding and access to information. This activity indicates that effective socialization can encourage public awareness and discipline in fulfilling tax obligations, which in turn supports the sustainability of regional development.